2014
DOI: 10.1111/pedi.12197
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of type 1 diabetes mellitus in 0 to 14-yr-old children in Croatia - 2004 to 2012 study

Abstract: The incidence of childhood T1DM is increasing in Croatia, thus placing Croatia among countries with high risk for T1DM. The annual increment of 5.87% is considerably lower than 9.0% reported earlier, but still higher than the European average (3.9%). The increase in incidence ceased in youngest children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Two youngest age groups (0-4 and 5-9 years) had the highest relative increase. This is in accordance with other studies reporting the increasing incidence of T1DM mostly in younger age group [11][12][13][14] , but is completely different from data reported in Croatia where the increase in the disease incidence ceased in the youngest children 15 . Similar to some other studies 16,17 , we found a steep increase in the incidence T1DM in Montenegro boys under five years of age.…”
Section: Discussionsupporting
confidence: 51%
“…Two youngest age groups (0-4 and 5-9 years) had the highest relative increase. This is in accordance with other studies reporting the increasing incidence of T1DM mostly in younger age group [11][12][13][14] , but is completely different from data reported in Croatia where the increase in the disease incidence ceased in the youngest children 15 . Similar to some other studies 16,17 , we found a steep increase in the incidence T1DM in Montenegro boys under five years of age.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, only a slight increase in the incidence of T1D was seen in the youngest children (aged 0‐4 years) and the rates remained stable in the years 2013 to 2014. In Croatia, for instance, the T1D in IR in the youngest children was found to increase by 2.43% a year, but that was still considerably lower than an annual increase by 14% reported previously . Other authors have also observed similar trends of a rapid annual increase in the number of new‐onset T1D cases among the youngest children followed by stabilization of the IRs .…”
Section: Discussionmentioning
confidence: 60%
“…found that the mean age at the time of Type 1 diabetes registration increased, but this was only examined in girls . In addition, in Croatia, the annual increase was lower (2.43%) and no statistically significant trend was found in the 0–4 years age group .…”
Section: Discussionmentioning
confidence: 90%